GC-MS analysis of metabolites from soxhlet extraction, ultrasound-assisted extraction and supercritical fluid extraction of Salacca zalacca flesh and its alpha-glucosidase inhibitory activity - Saleh, Mohammed S M; Mohd Bukhari, Dzatil Awanis; Siddiqui, Mohammad Jamshed Ahmad; Kasmuri, Abdul Razak; Murugesu, Suganya; Khatib, Alfi (Taylor & Francis, 2019)
ABSTRACT Different extraction processes were employed to extract bioactive metabolites from Salacca zalacca flesh by a range of aqueous and organic solvents. The highest extraction yield was obtained by 50% ethanol extract of SE (73.18 ±4.35%), whereas SFE_1 showed the lowest yield (0.42 ±0.08%). All extracts were evaluated for in vitro a-glucosidase inhibitory activity, measured by their IC50 values in comparison to that of quercetin, the positive control (IC50 ¼ 2.7 ±0.7 lg/mL). The lowest a-glucosidase inhibitory activity was indicated by water extract of SE (IC50 ¼ 724.3 ±42.9 lg/mL) and the highest activity was demonstrated by 60% ethanol extract by UAE (IC50 ¼ 16.2 ± 2.4 lg/mL). All extracts were analysed by GC-MS and identified metabolites like carbohydrates, fatty acids, organic acids, phenolic acids, sterols and alkane-based compounds etcetera that may possess the potential as a-glucosidase inhibitor and may attribute to the a-glucosidase inhibitory activity.